Experiences with Deploying VISIR at Al-Quds University in Jerusalem - Odeh, Salaheddin (2014)
Engineering and science labs play a central role in illustrating concepts and principles as well as improving technical skills. Through introducing of remote labs, it will be possible to share devices, equipment and instrumentations with lots of universities. Moreover, they relax time and space constraints and are capable to be adapted to pace of each student if there was insufficient time in lab; this contribution reports the experiences at Al-Quds University in Jerusalem in Palestine with deploying VISIR, and represents the results of an evaluation for its appropriateness as a complementary asset to traditional labs. The questionnaire for the interaction between students and VISIR includes survey questions with the goal to measure the evaluation criteria: usefulness and satisfaction, sense of reality/immersion and usability.